2014
DOI: 10.1093/abbs/gmu067
|View full text |Cite
|
Sign up to set email alerts
|

Expression of acid-sensing ion channels in nucleus pulposus cells of the human intervertebral disk is regulated by non-steroid anti-inflammatory drugs

Abstract: Non-steroid anti-inflammatory drugs (NSAIDs) are generally used in the treatment of inflammation and pain through cyclooxygenase (COX) inhibition. Mounting evidence has indicated additional COX-independent targets for NSAIDs including acid-sensing ion channels (ASICs) 1a and 3. However, detailed function and mechanism of ASICs still remain largely elusive. In this study, the impact of NSAIDs on ASICs in nucleus pulposus cells of the human intervertebral disk was investigated. Nucleus pulposus cells were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Non-steroid anti-inflammatory drugs (NSAIDs) were well-known non-specific inhibitors of ASICs, while Sun found that the NSAIDs could also regulate the expression of them in NPC [19]. After Ibuprofen treatment, the expression and current of ASIC1 and ASIC3 induced by acidic stress were suppressed, and the degeneration-induced cell death could also be prevented [19] (Table 3).…”
Section: Np Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-steroid anti-inflammatory drugs (NSAIDs) were well-known non-specific inhibitors of ASICs, while Sun found that the NSAIDs could also regulate the expression of them in NPC [19]. After Ibuprofen treatment, the expression and current of ASIC1 and ASIC3 induced by acidic stress were suppressed, and the degeneration-induced cell death could also be prevented [19] (Table 3).…”
Section: Np Degenerationmentioning
confidence: 99%
“…[11] ASIC3 was involved in adapting disc cells to their hydrodynamically stressed microenvironment, suggesting an additional role for this ASIC subunit. [19] Acidic pH causes a catabolic and degenerated phenotype in NPCs which is inhibited by blocking ASIC3 activity, suggesting that this may be a useful therapeutic target for treatment of IVD degeneration.…”
Section: Asic Isotypes Functional Description References Asic1amentioning
confidence: 99%
“…Currently, there are six isoforms of ASICs (Xiong et al, 2004 ; Yuan et al, 2010b ) and are activated by a decrease in the extracellular pH and are cation-selective. Recently it has been suggested that ASICs are expressed not only in nervous system but also in the non-neuronal cells, such as dendritic cells (Tong et al, 2011 ), astrocytes (Huang et al, 2010 ), vascular smooth muscle cells (Grifoni et al, 2008 ; Jernigan et al, 2012 ), nucleus pulposus cells (Ohtori et al, 2006 ; Uchiyama et al, 2007 , 2008 ; Navone et al, 2012 ; Cuesta et al, 2014 ; Sun et al, 2014 ), synoviocytes (Kolker et al, 2010 ), hepatic stellate cells (Wu et al, 2014 ), and glioma cells (Berdiev et al, 2003 ; Vila-Carriles et al, 2007 ; Kapoor et al, 2009 ). The wide expression pattern suggests that ASICs may have more diverse role in physiological and pathogenic processes.…”
Section: Mechanisms Of Acidosis Sensing and Its Regulation In Osteoclmentioning
confidence: 99%
“…One particular study, for example, showed that amiloride down-regulated the expression of ASIC-related proteins in human nucleus pulposus cells [7]. This study observed a similar outcome with NSAIDs, specifically ibuprofen [7].…”
Section: Acid Sensing Ion Channel (Asic) Pharmacologymentioning
confidence: 63%
“…One particular study, for example, showed that amiloride down-regulated the expression of ASIC-related proteins in human nucleus pulposus cells [7]. This study observed a similar outcome with NSAIDs, specifically ibuprofen [7]. Researchers demonstrated the clinical pain-relieving efficacy by amiloride where the subcutaneous injections of amiloride significantly attenuated the human pain response in those receiving painful proton iontophoresis [8].…”
Section: Acid Sensing Ion Channel (Asic) Pharmacologymentioning
confidence: 91%